Government Promotion of Renewable Energy Technologies Policy Approaches and Market Development in Germany, the United States, and Japan - Jordan-Korte, Katrin. (Gabler Verlag : Imprint: Gabler Verlag, 2011)
Renewable energy sources will play an increasingly important role in meeting global energy demand. Katrin Jordan-Korte presents the first comprehensive comparison of government promotion of renewable energy technologies in Germany, the United States, and Japan. The author expands the ongoing discussion of renewable energy use by also including an analysis of international markets of renewable energy technologies. She shows that the success of countries on those markets is positively correlated with a dynamic development on national markets for renewable energy use.